Effects of preoperative gabapentin on postoperative relief of pain in patients scheduled for surgery under general anaesthesia - Masar, Ritu; Arora, Kishore Kumar (International Journal of Research in Medical Sciences, 2019)
Background: To evaluate the effects of preoperative Gabapentin on postoperative relief of pain in patients scheduled for surgery under general anaesthesia. Post-operative ward and OT Department of Anaesthesia, JAH, GR Medical College, Gwalior, Madhya Pradesh, India. Methods: The sixty patients subjected to ASA grade I and II posted for elective surgeries under general anaesthesia were randomized into 2 groups. One and half hour before surgery, Gabapentin 600 mg and placebo was given blindly to selected patients for the study. The postoperative pain was assessed with visual analogue score. Pain and side effects assessment were performed. Results: Total 60 patients of ASA grade I and II posted for elective surgeries under GA were randomized into 2 groups. One and half hour before surgery, the drug selected for the study was given blindly with a sip of water. The mean (±SD) of VAS score was 5.86±0.34 in Group B and 5.10±0.84 in Group A. VAS score was significantly lower in Group A. With oral Gabapentin time required for rescue analgesia is delayed as compared to control group. The mean (±SD) TRA-1 was 38.40±24.61 in Group B and 44.03±8.94 in Group A. Conclusions: Preoperative oral Gabapentin significantly decreases the severity of pain postoperatively as compared to placebo in patients posted for surgery. Time for analgesic requirement is more with oral Gabapentin. The VAS score was lower in Gabapentin group.